Determination of prevalence of subclinical mastitis, characterization of intra-mammary infection-causing bacteria, and antibiotic susceptibility in dairy camels in Jigjiga City, Somali region, Ethiopia - Jama, Mohamoud Mohamed; Hussein, Hassan Abdi; Darod, Ziad Abdulahi; Ahad, Abdullahi Adan (Frontiers in Veterinary Science, 2024)
Background: Subclinical mastitis in camels, an inflammation of the udder without visible signs, can reduce milk quality and raise bacteria levels. Regular monitoring of camel milk is crucial for consumer safety.A cross sectional study was conducted in Jigjiga city, Ethiopia to investigate the prevalence and characteristics of subclinical mastitis in she-camels. The study included 244 lactating she-camels from three privately-owned camel dairy farms, and a questionnaire survey was conducted with 60 camel owners.The overall prevalence of subclinical mastitis in she-camels was 10.6% (26/244), with no significant difference among the studied dairy farms. Risk factors that influenced the result of California Mastitis Test (CMT) included age and udder and leg hygiene. The study revealed that S. aureus was the most prevalent bacterium among the isolated bacteria, with a prevalence rate of 34.5%. This was followed by S. agalactiae, S. dysgalactiae, and Pasteurella multocida, with prevalence rates of 29.8%, 19.4%, and 16.2% respectively. Among the isolated bacteria, 84.5% were sensitive to Erythromycin, 60% to Streptomycin, 44.7% to Oxytetracycline, and 36.7% to Tetracycline. Interviews with camel owners revealed that 66.7% used mixed herd grazing methods and reported feed shortage. Treatment practices for sick camels included modern veterinary drugs, traditional medicines, or a combination of both. The owners of camel dairy farms did not maintain proper hygiene practices during milking, such as not using soap when washing hands.: addressing camel mastitis necessitates access to alternative drugs, comprehensive herder training, and enhanced management practices.1